Inequalities in Educational Outcomes: How Important is the Family? - Julia Bredtmann; Nina Smith (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
In this paper, we investigate sibling correlations in educational outcomes, which serve as a broad measure of the importance of family and community background. Making use of rich longitudinal survey and register data for Denmark, our main aim is to identify the parental background characteristics that are able to explain the resemblance in educational outcomes among siblings. We find sibling correlations in educational outcomes in the range of 15 to 33 percent, suggesting that up to a third of the variation in educational achievement can be explained by family and community background. Our results further reveal that parents socio-economic background (i.e., their education, occupation, and income) can explain up to 44 percent of the sibling correlation. However, non-economic factors such as family structure, the incidence of social problems, and parents educational preferences also play an important role for sibling similarities in educational outcomes.
Keywords: I21; I24; J13; 330